1998
DOI: 10.1159/000025841
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide Enhances IL-1β-Stimulated Nitric Oxide Production in Cultured Rat Vascular Smooth Muscle Cells

Abstract: Objective: To elucidate the effect of atrial natriuretic peptide (ANP) on cytokine-induced nitric oxide (NO) production, we examined whether ANP affects IL-1β-stimulated NO production and inducible NO synthase (iNOS) mRNA expression in cultured rat vascular smooth muscle cells (VSMC). Methods: VSMC were incubated with test agents for 24 h. The nitrite concentration of the culture medium, a stable-end product of NO, was measured by the column reduction method. NOS mRNA expression was analyzed by Northern blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…In fact, incubation of SMCs with the PKA inhibitor KT 5720 abolishes the sildenafil-mediated increase in NO synthesis in cytokine-exposed cells. These results are in-line with earlier reports showing that PKA mediates the augmentation of cytokine-induced NO generation in vascular SMCs by activators of guanylate cyclase [36,37]. Furthermore, the ability of KT 5720 to suppress NO synthesis following cytokine treatment is consistent with a previous study showing a critical role for PKA in mediating the induction of iNOS by cytokines [38].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, incubation of SMCs with the PKA inhibitor KT 5720 abolishes the sildenafil-mediated increase in NO synthesis in cytokine-exposed cells. These results are in-line with earlier reports showing that PKA mediates the augmentation of cytokine-induced NO generation in vascular SMCs by activators of guanylate cyclase [36,37]. Furthermore, the ability of KT 5720 to suppress NO synthesis following cytokine treatment is consistent with a previous study showing a critical role for PKA in mediating the induction of iNOS by cytokines [38].…”
Section: Discussionsupporting
confidence: 92%
“…In cultured rat VSMC, we found that cGMP-generating agents, including ANP, could enhance the IL-1β-induced NO production through activation of protein kinase A [12]. In the present study, ticlopidine increased both cyclic nucleotides.…”
Section: Discussionsupporting
confidence: 60%
“…We also reported that erythropoietin (EPO) inhibited the iNOS mRNA expression and protein via activation of protein kinase C [9, 10]. Conversely, both atrial natriuretic peptide and cGMP enhanced IL-1β-induced NO production in VSMC, possibly through activation of cAMP-dependent protein kinase [11, 12]. With regard to cyclic nucleotides, cyclic 3′,5′-adenosine monophosphate (cAMP) is known to have a potency to stimulate iNOS mRNA expression and NO production [13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…64 ANP was first identified as a diuretic/natriuretic and vasodilating hormone, 65 but subsequent studies revealed that ANP has various cardioprotective effects such as antiapoptosis, antifibrosis, and antihypertrophy not only as circulating hormones but also as local autocrine and/or paracrine factors. 66 -68 ANP has been reported to accelerate nitric oxide generation, 69,70 which mediates late preconditioning. Furthermore, ANP activates the reperfusion injury salvage kinase, which acts like ischemic preconditioning and postconditioning.…”
Section: Atrial Natriuretic Peptide and Brain Natriuretic Peptidementioning
confidence: 99%